Are They There Yet? Revisiting the Accuracy Level of Computer-Generated Translation - Asep Suparman (Politeknik Negeri Padang, 2020)
Speed, cost, and quality have been the central issues in the translation industry. While computers can offer fast and economical translation, their ability to produce accurate translation at a publishable level like human translators may do is still questionable. In the present study, the author linguistically evaluated the accuracy of English to Indonesian translation generated by Google Translate. Freely accessible English texts of various types were chosen to heuristically exemplify the units of analysis. The results of analysis lead to the conclusion that although Google’s Neural Machine Translation system is quite an improvement to the conventional phrase-based translation system, highly accurate translation does not seem to be achieved by Google Translate in the near future.